Formation and Development of Artificial Intelligence (Eurasian Journal of Research, Development and Innovation, 2023)
In this article, you will learn about "artificial intelligence" which has become a hot topic these days. In the article what is artificial intelligence?, History of artificial intelligence, stages of development?, Is artificial intelligence a threat to humanity?, What is its positive or negative impact on society? How can artificial intelligence be used in various fields today? We will try to find answers to such questions